The Problems and Forthcoming Ideal Concepts of Employment Social Security: An Indonesia’s Perspective as a Welfare State - Nyoman Satyayudha Dananjaya; Anak Agung Gede Duwira Hadi Santosa; Kadek Agus Sudiarawan; Made Dwita Martha (Fakultas Hukum Universitas Mataram, 2022)
The Procedures and Requirements for Payment of Old Age Security stated that the benefits of Old Age Security at the Institution of Social Security Employment can only be taken when workers enter retirement or at the age of 56 years, which elicits opposition reactions from various parties. The focus of this research was conducted to examine and criticize whether the Old Age Security (OAS) and Job Loss Guarantee (JLG) policies for workers who have been terminated have reflected the conception of an Indonesian welfare state that is socially just for all Indonesians, as well as to find out how the future concept (Ius Constituendum) of OAS and JLG for workers reflects the welfare state for social justice. A statutory and conceptual approach are used to support the type of normative legal research in this research. The results of the study indicate that the OAS and JLG policies have not described the concept of an Indonesian welfare state with social justice. To describe the OAS and JLG policies that reflect the welfare state, future policies must still provide convenience for workers to receive OAS benefits and continue to carry out OAS benefits.